Optics design for Electron Cyclotron Emission Imaging system on J-TEXT. (31st May 2016) - Ma, X.D.; Yang, Z.J.; Zhu, Y.L.; Pan, X.M.; Xiao, Y.; Ruan, B.W.; Zhuang, G.; Xie, J.L.
Abstract: An electron cyclotron emission imaging (ECEI) system is being developed for J-TEXT. It is comprised of two 16-channel antenna arrays that share the same toroidal window for the purpose of observing separate radial regions of the tokamak plasma simultaneously. Two imaging optic units have been designed, which share the same zoom lenses, but have different focus lenses. The setup is flexible and achieves good spatial resolution. In particular, the poloidal zoom factor can achieve 1.17 to 2.20. The desired focal plane can range anywhere from high field side (HFS) edge to low field side (LFS) edge. The effective field curvature adjustment (FCA) lenses have been adopted for the ECEI imaging optic system, which make the image plane flat enough to match the emission layer in order to increase the image quality.